Decomposing the Role of Rehearsal in Auditory Distraction during Serial Recall. Issue 1 (2nd April 2020) - AuBuchon, Angela M; McGill, Corey I.; Elliott, Emily M.
ABSTRACT: According to the interference-by-process mechanism of auditory distraction, irrelevant changing sounds interfere with subvocal articulatory-motor sequencing during rehearsal. However, previous attempts to limit rehearsal with concurrent articulation and examine the residual irrelevant sound effect have limited both cumulative rehearsal as well as the initial assembly of articulatory-phonological labels. The current research decomposed rehearsal into these two levels of articulatory-phonological sequencing: silent concurrent articulation limits the availability of both serial repetition and articulatory-phonological recoding; rapid serial visual presentation allows for articulatory-phonological recoding but presents items too quickly for cumulative serial repetition. As predicted by the interference-by-process account, concurrent articulation – but not rapid serial visual presentation – reduced the irrelevant sound effect. Not only did the irrelevant sound effect persist in the face of rapid serial visual presentation, a steady-state effect also emerged. These findings indicate that irrelevant sounds interfere with both serial processing of articulatory-motor planning at the word level as well as in the formation of item-to-item associations created via serial repetition of complete items. Moreover, these findings highlight the benefits of articulatory-phonological recoding – independent of pure rehearsal – within serial recall.